City resilience strategies in dealing with the aftermath of the COVID-19 pandemic: Using socio-ecological systems - Fitrianto, Achmad Room; Hasna Anugerah Viola (C-DISC, 2023)
Many aspects of human life have been changed by the COVID-19. Urban development model is one of the various changes. Therefore, it is necessary to formulate strategies or policies related to landscape and urban management. This writing study the concept of urban resilience in dealing with the post COVID-19 pandemic using a socio-ecological system to provide strategies related to these problems. This study uses a qualitative descriptive method by collecting data sources from the literature study. The data analysis used content analysis techniques. The study provides critical analysis in terms of the city's resilience strategy in dealing with the postCOVID-19 pandemic using a socio-ecological systems approach. There are three elements or strategies are found, namely economic resilience, consumer behavior (society adaptation), and environmental changes.